Effects of Enrichment and Litter Parity on Reproductive Performance and Behavior in BALB/c and 129/Sv Mice - Whitaker, Julia W (J Am Assoc Lab Anim Sci, 2016)
We examined the effect of adding species-appropriate environmental enrichment items to breeding cages of BALB/cAnNCrl and 129S2/SvPasCrl mice. The 3 enrichment conditions were: 1) cotton nesting material; 2) nesting material plus a paper shelter and rolled paper bedding; and 3) an igloo dome with an exercise wheel in addition to the shelter-group enrichments. We measured litter size, litter survival to weaning age, average pup weight at 21 d, and the interlitter interval to evaluate reproductive performance. A random subset of the first- or second-litter offspring from each enrichment condition and strain was assessed in multiple behavioral tests. Enrichment significantly affected anxiety-like behavior and sociability, with the direction of change dependent on strain and sex. Litter parity had greater effects on some reproductive parameters than did the enrichment condition, and this effect was not solely due to a difference between the first compared with subsequent litters. The significant effects of litter parity on the number of pups born and weaned, female pup weight, and interlitter interval were dependent on the enrichment condition in BALB/c but not 129/Sv mice. Offspring from the first or second litter were included in a generational component to investigate whether enrichment effects on reproduction persist in adult offspring after transfer to a different facility for breeding. Natal cage enrichment had no effect on any reproductive parameter in the transferred mice. Overall, additional enrichment beyond nesting material had a beneficial effect on the interlitter interval in BALB/c mice and on the number of pups weaned in 129/Sv mice.